2019
DOI: 10.4236/ym.2019.32015
|View full text |Cite
|
Sign up to set email alerts
|

Successful Management of Preterm Premature Rupture of Membrane in Second Trimester: A Case Report and Literature Review

Abstract: The preterm premature rupture of membranes occurring in early pregnancy at less than 23-24 weeks (prior to fetal viability), has higher risk for early preterm delivery, and therefore, the poorer the prognosis with poor chance of neonatal survival and a high rate of severe, long-term neonatal morbidity among survivors. In such cases in absence of overt evidence of intrauterine infection at the time of diagnosis termination of pregnancy or expectant management is generally offered modality of treatment, the prio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…These findings showed that the earlier in gestation the rupture occurs, the less likely labor will begin inside the time periods specified. 14,30 El Sokkary et al study noted a positive correlation among cervical length and latency interval. Mehra et al reported that shorter transvaginal cervical length independently predicts delivery within 7 days in women with PPROM.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…These findings showed that the earlier in gestation the rupture occurs, the less likely labor will begin inside the time periods specified. 14,30 El Sokkary et al study noted a positive correlation among cervical length and latency interval. Mehra et al reported that shorter transvaginal cervical length independently predicts delivery within 7 days in women with PPROM.…”
Section: Discussionmentioning
confidence: 95%
“…13,22,26 Researchers found that a dynamically changing cervix increases the accuracy of cervical length in predicting preterm birth, either spontaneously or in response to fundal pressure. 14,15 The many dynamic cervical assessment techniques include the Valsalva maneuver, cervical length ultrasonography, contraction monitoring during a 10minute period, and watching the change in the cervical appearance in response to fundal pressure for 15 seconds. During a 5-minute TVUS cervical scan, there may be spontaneous funnelling.…”
Section: Introductionmentioning
confidence: 99%